2022
DOI: 10.1002/jcla.24507
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic score model based on six m6A‐related autophagy genes for predicting survival in esophageal squamous cell carcinoma

Abstract: Background: Prognostic signatures based on autophagy genes have been proposedfor esophageal squamous cell carcinoma (ESCC). Autophagy genes are closely associated with m6A genes. Our purpose is to identify m6A-related autophagy genes in ESCC and develop a survival prediction model. Methods: Differential expression analyses for m6A genes and autophagy genes were performed based on TCGA and HADd databases followed by constructing a co-expression network. Uni-variable Cox regression analysis was performed for m6A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…TCGA-acquired data also included expression data for 23 M6A-related genes, including eight writer genes (METTL16, METTL3, METTL14, RBM15B, WTAP, RBM15, VIRMA, and ZC3H13), 13 reader genes (FMR1, HNRNPC, HNRNPA2B1, IGF2BP3, IGF2BP2, IGF2BP1, LRPRRC, RBMX, YTHDF3, YTHDF2, YTHDC2, YTHDC1, and YTHDF1), and two eraser genes (ALKBH5 and FTO) A . The anatomic stage was determined based on the criteria published by the American Joint Committee on Cancer (AJCC) Staging Manual, 8th edition (2017) [15].…”
Section: Methodsmentioning
confidence: 99%
“…TCGA-acquired data also included expression data for 23 M6A-related genes, including eight writer genes (METTL16, METTL3, METTL14, RBM15B, WTAP, RBM15, VIRMA, and ZC3H13), 13 reader genes (FMR1, HNRNPC, HNRNPA2B1, IGF2BP3, IGF2BP2, IGF2BP1, LRPRRC, RBMX, YTHDF3, YTHDF2, YTHDC2, YTHDC1, and YTHDF1), and two eraser genes (ALKBH5 and FTO) A . The anatomic stage was determined based on the criteria published by the American Joint Committee on Cancer (AJCC) Staging Manual, 8th edition (2017) [15].…”
Section: Methodsmentioning
confidence: 99%
“…The training set and validation set were downloaded via the Gene Expression Omnibus (GEO) ( https://www.ncbi.nlm.nih.gov/gds ) database, in which the contained 33 NAFLD samples and 34 normal samples (samples type: liver wedge biopsy) ( Xanthakos et al, 2015 ), and validation set contained 72 NAFLD samples and three normal samples (samples type: liver biopsy) ( Hoang et al, 2019 ). Additionally, 232 autophagy-related genes (ARGs) were extracted from the human autophagy database (HADb) ( Chen et al, 2022 ) ( http://www.autophagy.lu/ ), and 37 m6A were obtained from the literature ( Li et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies indicated that YTH domaincontaining proteins act as potential diagnostic biomarkers in patients with cancer [90][91][92][93]. Chen et al [94] examined differentially expressed m 6 A and autophagy genes in esophageal squamous cell carcinoma (ESCC). They developed and validated a predictive model based on six characteristic autophagy genes for predicting the survival of patients with ESCC.…”
Section: Potential Diagnostic Value Of M 6 a Modification In Regulati...mentioning
confidence: 99%